Understanding nitrogen dynamics in coral holobionts: comprehensive review of processes, advancements, gaps, and future directions - Li, Moyang; Sheng, Hua-Xia; Dai, Mengyao; Kao, Shuh-Ji (Frontiers in Marine Science, 2023)
Coral reefs are known for being highly productive ecosystems in oligotrophic oceans, which is commonly referred to as the Darwin’s Paradox. Nitrogen is an essential component of organisms, but it limits primary productivity in most euphotic ocean, including the coral reef system. Therefore, understanding nitrogen’s transfer and transformation within the coral holobiont is essential to comprehend the holobiont homeostasis and functioning mechanisms, which may help to explain the Darwin’s Paradox. Previous studies have pointed out the fundamental importance of nitrogen cycling between coral host and symbiotic algae. Recently, increasing researches, particularly in quantitative aspect, have significantly improved our understandings of the various roles of nitrogen pathways in regulating the inter-relationship among coral host and symbiotic algae and the associated microbiome. In this paper, we synthesized knowledge advances of different nitrogen processes in coral holobionts standing on the nitrogen cycle perspective. We extracted consensus and contradictions from published research results regarding nitrogen flows of coral holobiont. This review presented the temporal and spatial variation of nitrogen fixation and analyzed the global nitrogen processes rates in coral holobionts. We also summarized projections of specific nitrogen processes of coral holobionts facing climate change from limited reports. We realized that there are significant gaps in our understanding of nitrogen processes in coral holobionts, which hindering our comprehension of nitrogen balance in coral holobionts and, therefore, the coral reef systems. These gaps include the roles and relative importance of nitrification, denitrification, and DNRA in coral holobionts, as well as the self-regulation mechanisms to maintain nitrogen-homeostasis in short-term and long-term, particularly in the context of environmental changes. At the end, we provide our opinions on research methods regarding quantitative coral research in the future.